Outward direct investment versus technology licensing: an SME perspective - Szalavetz, Andrea (Competitio, 2010)
Based on the example of the evolution and internationalization of a Hungarian wastewater treatment company, this paper investigates various theoretical and strategic management issues. As for thetheoretical part, Hungary’s outward direct investment performance is analyzed departing from the thesis that Hungary’s present seemingly favorable OFDI performance is just a statistical artifact. It isonly organic development, based on local entrepreneurs’ capital export that can substantiate Hungary’s present OFDI position. The strategic management issues analyzed in the paper include the sequencing of internationalization; the pitfalls related to growth; modes of foreign market entry; and the choice between FDI-based internal exploitation of technological knowledge and external technology exploitation in the form of technology licensing.JEL codes: F23, L24, L26, O16, O33, Q57